Badagas of the blue mountains : ... their unique history, origin, culture, customs, rituals, language and lifestyle! (2006)
[Dt.:] Badagas, deren Ursprünge nach wie vor für viele Wissenschaftler von besonderem Interesse. Kultur und Sprache Badaga (badagu) werden auf dieser Seite präsentiert. Diese Seite widmet sich voll und ganz dieser tribalen Gesellschaft der Niligiriberge in Tamil Nadu und Karnataka. - [Engl.:] The study on Badagas, whose origin is still a source of study for many western researchers, is very fascinating because of their unique customs, culture and language which is also known as Badaga (badagu). Though, much information is available on the net, there is no single or specific website that tells all that is known and unknown about Badgas. This website focusses on this 'tribal' community mainly living in the hilly regions of the Nilgiris in South India and in parts of Tamil Nadu and Karnataka.